The Distribution of Heirless Books to Morocco by the Jewish Cultural Reconstruction, Inc. - Guedj, David (Zutot, 2018)
This article looks into the one-of-a-kind encounter between the inter-diasporic Jewish corporation Jewish Cultural Reconstruction (JCR), and the Alliance Israélite Universelle’s (AIU) Hebrew teachers’ seminary in Casablanca, an encounter that studies into JCR’s history have all but failed to cite. Nevertheless, Morocco’s case is of considerable significance, Morocco being the only Islamic country where the Jewish community managed to obtain books from JCR. This unique case warrants a review into what facilitated the encounter between the seminary and the corporation, and an examination in light of broader historic processes that took place as part of the Moroccan Jewish relations with other diasporic Jews.